Cyanocobalamin Restores Heat Stress - Induced Immune Organs & Hematological Parameters in Albino Rats - Abdul Hafeez Daft, Anjum Naqvi, Syed Murtaza , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objective; To determine the deleterious effects of heat-stress on the immune organs and hematological parameters and to evaluate the anti—stress and inimunomodulatory role of the Cyanocobalamin. Place and duration of the study: Experimental study conducted in the department of Anatomy, Ra0c Medical Sciences Institute, Jinnah Postgraduate Medical Centre, Karachi from December 2010 to March 2011. Material and Methods: Forty five Albino rats (180-200 grams) were selected and divided into group (Control), group B (Heat - Stressed) and group C (Protective). Each group was further subdivided into three subgroups, based on the period ofthe study. The animals ofthe subgroups B and C received heat and the temperature was set at 42`.0 for six hours daily. Group C (Cl, C2 and C3) animals were protected with Cyanocobalamin at the dosage of 0.8 mg/ kg of body weight intraperitonealy, two hours before heat induction. Then animals were sacrificed according to their time duration, and spleens were examined grossly for any change in shape, color, consistency, and hemorrhagic spots. Blood samples were collected from each animal by cardiac puncture in the plastic vacutainers containing EDTA-K2 as an anticoagulant( BD- Franklin NJ, USA) for the total leucocyte count ( TLC) and differential leucocyte count ( DLC). Results: Heat—stress and its consequences significantly decrease the size of the spleen in all subgroups of group B animals. It could be due to decrease in appetite, decrease feed intake and catabolism of proteins due to excessive ACTH and corticosterone secretion as HPA axis stimulated by heat-stress. Same hormones also affect severely the all lines of the white blood cells. The prophylactic use of the Cyanocobalamin in group C animals restores the normal size of the spleen and the normal count of white blood cells by its cell repairing, cytoprotective and anti-apoptotic role. Conclusion: Heat-stress severely damages the immune organs and suppresses the bone marrow function. Cyanocobalamin (Vitamin B 12 ) in its pharmacological concentration has expressed itself as an immunopotentiating and anti-stress agent, It restores the immunoarchitecture, their cell count and also enhances the magnitude ofthe bone marrow activity.